Mesenchymal stem cell-derived extracellular vesicles enriched with miR-124 exhibit anti-inflammatory effects in collagen-induced arthritis - Guo , Zhonghua; He, Mengyuan; Shi , Dongliang; Zhang, Zhongbo; Wang, Lisha; Ren, Bowen; Wang , Yunfei; Wang, Junjie; Yang , Shaoxiang; Yu, Hongchao (Archives of Biological Sciences, 2024)
Paper description: Rheumatoid arthritis (RA) is a chronic inflammatory disease treated with limited success. Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) may help by secreting anti-inflammatory factors. We investigated whether human umbilical cord MSC-EVs overexpress miR-124 using lipofectamine 3000 could enhance their therapeutic potential. EVs enriched with miR-124 reduced disease severity in a mouse model of arthritis, by modulating inflammatory cytokines. MSC-EVs that overexpress specific miRNAs offer a promising cell-free approach for optimizing the treatment of inflammatory joint diseases. Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by joint inflammation, leading to pain, swelling, stiffness, and joint damage. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) hold significant promise as therapeutic agents owing to their potent paracrine activities. This study investigated the anti-inflammatory effects of human umbilical cord-derived MSC (hUCSC)-EVs overexpressing miR-124 in collagen-induced arthritis (CIA). hUCSCs were transfected with miR-124, and hUCSC-EVs were isolated and characterized. Arthritis was induced in mice by collagen injection, followed by intravenous administration of miR-124 EVs, miR-control, or vehicle. Cytokine levels, including interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, IL-10, and transforming growth factor (TGF)-β, were measured in the joints using real-time PCR by enzyme-linked immunosorbent assay (ELISA). miR-124-hUCSC-EVs showed enrichment of miR-124. In arthritic mice, intravenous treatment with miR-124 EVs significantly reduced the clinical score, increased anti-inflammatory cytokines IL-10 and TGF-β, and lowered inflammatory cytokines IL-6, TNF-α, and IL-1β in the joints. This study shows that miR-124 EVs have anti-inflammatory activity in arthritis by suppressing pro-inflammatory cytokines through miR-124 overexpression. MSC-EVs overexpressed with inflammation-modulating miRNAs offer a promising cell-free approach for treating inflammatory arthritis.